(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
Gender inequality in education remains one of the key problems of modern society. The article examines the main causes and consequences of inequality, analyzes existing research and suggests possible solutions to the problem. The study relies on quantitative and qualitative methods, allowing to identify the main patterns and their impact on society. The obtained results can contribute to the development of strategies to reduce the gender gap in education.